Volatility in Quarterly Accounting Data. - Kiger, Jack E. (The Accounting Review, 1974)
Abstract The article discusses a study of the different approaches to reporting interim accounting data. Although the accounting literature has posited three approaches, there are only two alternative concepts of distinguishing net income. These are the independent period concept, and the dependent period concept. The first gives status similar to that of the annual period so that traditional accounting principles are applied in income determination. The second views the interim period as part of the annual period.